Natural products repository of Costa Rica (NAPRORE-CR): an open-access database - Acuña Jiménez, Daniel Alonso (2025)
Natural products are outstanding resources of bioactive compounds with potential applications not only in drug discovery but also in the cosmetic industry and natural pesticides. Costa Rica is among the most biologically diverse countries in terms of the number of known species per unit of area, even above conventionally considered megadiverse countries. In this work, we introduce the Natural Products Repository of Costa Rica (NAPRORE-CR): the first dedicated database that compiles structural representations and predicted properties of natural products found and/or characterized in Costa Rica. The first version of this collection comprises 1161 compounds, annotated with structural classifications, calculated structural and physicochemical properties (MW, HBD, HBA, RB, AlogP, and TPSA), and complex descriptors (SA score, QED, nSPS). The diversity and chemical space coverage of compounds in NAPRORE-CR were compared to drugs, pesticides, and cosmetics. Through the analysis and visualization of chemical space coverage and diversity, it was found that NAPRORE-CR has a property profile compatible with applications in all three fields, and that its compounds are structurally similar to those of approved drugs and natural pesticides. Cross-referencing NAPRORE-CR with PubChem and ChEMBL, combined with activity predictions, facilitated the identification of both known applications of the included compounds and potential new areas of study. In favour of open science and FAIR principles for data sharing, NAPRORE-CR is freely available at https://doi.org/10.5281/zenodo.7858061.